Plz help...
6b - 49 =2(b - 3)



5 years ago Comment

You always start by simplifying.
6b-49=2(b-3) becomes 6b-49=2b-6
From there you can group the b's together by subtracting 2b from both sides, leaving you with 4b-49=-6
Now you can get the b's alone by adding 49 (to cancel out -49) to both sides, giving you 4b=43, You're still trying to get b by itself, so what you'll do is divide both sides by 4, giving you b=10.75


5 years ago Comment

[latex] 6b - 49 =2(b - 3)\\ 6b-49=2b-6\\ 4b=43\\ b=\frac{43}{4}[/latex]